The effects of nominal maximum aggregate size on the properties of hot mix asphalt using gyratory compactor - Chong, Elizabeth Eu Mee (2006)
The introduction of Superpave mix design in 1993 in the United States has categorized mixes based on the nominal maximum aggregate size (NMAS). The centerpiece of the mix design is the Superpave Gyratory Compactor (SGC). Properties of hot mix asphalt (HMA) have always been associated with pavement deformations. This study looks into the effects of NMAS on the properties of Malaysian HMA mixtures, which includes optimum bitumen content (OBC), bulk specific gravity (Gmb), theoretical maximum density (TMD), water absorption (WA), voids in mineral aggregate (VMA), voids filled with bitumen (VFB), and dust to binder ratio (D:B). Thus, a better understanding of the properties can reduce the pavement deformations. A total of four asphaltic concrete mix designs with different NMAS were prepared in accordance with the JKR Specification, namely AC10, AC14, AC20, and AC28. Specimens of each mix design with varying bitumen content were compacted to 75 and 100 gyrations using SGC to obtain 4Â±1% air voids. It was observed that as the NMAS increased, the OBC and VMA decreased. The Gmb, TMD, WA, and D:B showed opposite trend of the earlier properties. T-tests indicated that all properties except VMA were affected by NMAS. VMA for AC20 failed the minimum requirement initially but when calculated using the average asphalt film thickness method, it was acceptable. Different compaction efforts showed the same pattern on the properties except VFB while t-tests revealed that OBC, TMD, VMA, and D:B were significantly affected. Investigation also showed that AC20 is the best mix from the economic and durability point of views